Choroidal thickness as determined via in vivo imaging technique in relation to degree of myopia, axial length and vitreous chamber depth in Malay subjects - Mohd Zamri, Khayrin Adlina; Othman, Shah Farez; Ithnin, Mohd. Hafidz; Hajar Maidin, Mohamad Hanif (CEDEC Training Sdn. Bhd., 2023)
Anatomical changes of the eye associated with myopia have been studied intensively in recent years. The first distinguishing feature of axial myopia is the monotonic increment of axial length together with refraction. The purpose of this study was to determine the relationship between choroidal thickness (CT) with degree of myopia (SER), axial length (AL) and vitreous chamber depth (VCD) in Malay subjects. Forty-seven (47) Malay subjects (aged 19-20 years) with mean SER of -1.38 ± 0.27 D, mean axial length of 23.58 ± 1.35 mm and mean vitreous chamber depth of 20.30 ± 0.12 mm were included in this clinical cross-sectional study. The macular thickness results from the Topcon swept-source OCT were used to determine the thickness of choroidal areas manually at 9 quadrants, i.e., fovea, inner nasal, inner temporal, inner superior, inner inferior, outer nasal, outer temporal, outer superior and outer inferior to the fovea. The 9 quadrant is located at 1 mm, 3mm and 6 mm in diameter to the central point of the fovea. Positive correlation was found between CT and SER at five locations which are at fovea (rs = 0.31, p < 0.05), outer nasal (rs = 0.60, p < 0.05), inner nasal (rs = 0.40, p < 0.05), outer inferior (rs = 0.45, p < 0.05), and inner inferior (rs = 0.46, p <0.05). Also, negative correlations were found between CT and AL at outer nasal (rs = -0.46, p < 0.05), inner nasal (rs = -0.31, p <0.05) and outer inferior (rs = -0.41, p < 0.05). Furthermore, negative correlations were also found between CT and VCD at outer nasal (rs = -0.51, p < 0.05), inner nasal (rs = -0.32, p <0.05) and outer inferior (rs = -0.38, p < 0.05). This study shows that the degree of myopia and elongation of the globe are associated with thinning of certain choroidal areas. Therefore, the higher the degree of myopia, the choroidal vasculature will be thinner.